Effect of laser photobiomodulation on the periodontal repair process of replanted teeth - Matos, Felipe de Souza; Godolphim, Fernanda de Jesus; Oliveira Correia, Ayla Macyelle de; Cavalcanti de Albuquerque Junior, Ricardo Luiz; Paranhos, Luiz Renato; Rode, Sigmar de Mello [UNESP]; Gonzaga Ribeiro, Maria Amalia (Wiley-Blackwell, 2016)
Background/Aim: Tooth replantation is the optimal treatment in cases of avulsion. However, its success is limited due to the occurrence of external root resorption. The aim of this study was to assess the effect of laser photobiomodulation (LPBM) at k808 nm and k660 nm and of storage media on the periodontal repair process of replanted teeth in rats. Material and methods: Sixty maxillary right incisors were extracted from sixty Wistar rats and randomly assigned to six groups (n = 10). Groups consisted of 10 teeth stored in paper napkins (PN), whole milk (WM), and soy milk (SM), for 45 min; and PNL, WML and SML, in which teeth were stored in the same storage media, but the root surface and the alveolus were treated with LPBM at k808 nm before replantation, and the buccal and palatal mucosa of the alveolus were treated with LPBM at k660 nm after replantation. Five rats from each group were euthanized after 15 or 30 days. The right hemimaxilla including the replanted incisor was removed and processed for histomorphometric analysis to assess root resorption areas, replacement root resorption, perimeter with ankylosis and periodontal repair, and areas of type I and III collagen deposition, using the ImageJ 1.50b software. Data were analyzed statistically by ANOVA followed by Tukey's multiple comparison test (alpha = 5%). Results: WM and SM showed smaller root resorption areas and higher collagen deposition in both experimental periods, and SM showed the largest perimeter of periodontal repair. LPBM reduced the occurrence of root resorption only in the PNL group, both at 15 and 30 days, and increased the perimeter of periodontal repair in all groups at 30 days. There was higher collagen deposition in the irradiated groups regardless of the experimental period. Conclusions: The LPBM protocol at k808 nm and k660 nm as well as whole milk and soy milk favored the periodontal repair process of replanted teeth in rats.
Keywords: tooth avulsion; tooth replantation; lasers